2022
DOI: 10.2196/36275
|View full text |Cite
|
Sign up to set email alerts
|

Using Personalized Avatars as an Adjunct to an Adult Weight Loss Management Program: Randomized Controlled Feasibility Study

Abstract: Background Obesity is a global public health concern. Interventions rely predominantly on managing dietary intake and increasing physical activity; however, sustained adherence to behavioral regimens is often poor. The lack of sustained motivation, self-efficacy, and poor adherence to behavioral regimens are recognized barriers to successful weight loss. Avatar-based interventions achieve better patient outcomes in the management of chronic conditions by promoting more active engagement. Virtual re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Another group of applications prevails in the areas of obesity and eating disorders were visualizations of humanoid avatars are now being included in patient evaluation and management studies. Horne et al [22] found that seeing a "future self" in the form of a personalized avatar reinforced motivation to modify behavior and promote engagement in a weight loss program. Three-dimensional avatars are also being used to visually map body image perceptions as an objective means of revealing anorexia nervosa illness severity [20,21,30].…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Another group of applications prevails in the areas of obesity and eating disorders were visualizations of humanoid avatars are now being included in patient evaluation and management studies. Horne et al [22] found that seeing a "future self" in the form of a personalized avatar reinforced motivation to modify behavior and promote engagement in a weight loss program. Three-dimensional avatars are also being used to visually map body image perceptions as an objective means of revealing anorexia nervosa illness severity [20,21,30].…”
Section: Potential Applicationsmentioning
confidence: 99%